Mentoring the Preparation of 4 Anti Programs (No Sexual Violence, No Bullying, No Intolerance, and No Corruption) for Elementary School Students at SDN BENDO 01 - Rarasati, Ida Putri; Rosyida, Desy Anindia; Putri, Erica Panggayuh (Society : Jurnal Pengabdian Masyarakat, 2025)
Community service activities as a form of implementation of the Tri Dharma of Higher Education which is carried out by involving lecturers, students and partner institutions. In this community service with the title "Mentoring the Preparation of the 4 Anti Programs (No Sexual Violence, No Bullying, Intolerance, and No Corruption) for Elementary School Students at SDN Bendo 01" as a form of community service activities carried out in collaboration with it.  This community service activity began with field observations of the situation and condition of student characters at SDN Bendo 01 by observing students' daily behavior at school, both in interacting with teachers and peers. Observations were made starting from learning activities, and student interactions in and outside the classroom. After obtaining information about the development of SDN Bendo 01 students, a schedule was prepared for mentoring class teachers and subject teachers to participate in this activity on a scheduled basis. It is hoped that all teachers can prepare and implement no violence programs in the school environment and the surrounding community.  The final result of this community service activity is the preparation of no violence guidelines in schools both in classroom and outside classroom learning activities. So it is hoped that with these guidelines it will make it easier for teachers to develop good character in students and make it easier for students to behave in the school environment and the community.